Analysis of transcription of the human Alu family ubiquitous repeating element by eukaryotic RNA polymerase III. - Fuhrman, S A (1981)
A series of clones that contain human Alu family elements are actively transcribed in soluble in vitro RNA polymerase III systems. The 5' ends of the in vitro transcripts are located about 170 nucleotides upstream of the eponymous Alu I site of the repeat, while a region associated with specifying of the initiation site for in vitro transcription lies in the region between 79 and 106 nucleotides upstream of the central Alu site. Thus, the RNA polymerase III transcription unit defined by the human Alu family is similar to other RNA polymerase III transcription units in possessing an internal region that is required for active transcription in vitro.